Asymmetric Synthesis of Netarsudil: A New Therapeutic for Open-Angle Glaucoma - deLong, Mitchell A.; Sturdivant, Jill M. (Synthesis, 2019)
The asymmetric synthesis of a Rho kinase/norepinephrine transport inhibitor, netarsudil, the active component in the recently FDA-approved product Rhopressa™, is described herein. This concise six-step synthetic route utilizes the 2,4-dimethylbenzoate ester of a phenylacetic acid as the backbone of the β-amino acid’s framework. A chiral enolate of the Evans auxiliary, (R)-4-benzyloxazolidin-2-one, is used to direct the formation of the (S)-stereocenter by incorporating the N-Boc-protected β-amino methyl arm with high diastereoselectivity (96:4 dr) using N-Boc-1-aminomethylbenzotriazole as the electrophile. Uniquely, 2,2,2-trichloro-1,1-dimethylethyl chloroformate is used as a non-racemizing activating agent for the coupling reaction between the chiral (S)-N-Boc-protected 2,4-dimethylbenzoyloxymethyl phenyl propanoic acid and 6-aminoisoquinoline to provide N-Boc-protected netarsudil in good yield and excellent enantiomeric purity (63%, 98% ee). Final acidic deprotection and recrystallization provides netarsudil (>99% ee), an ophthalmic agent used for the treatment of patients with open-angle glaucoma.
Keywords: netarsudil; ROCK; Rho kinase; β-amino acids; glaucoma